1979
DOI: 10.1111/j.1755-3768.1979.tb01830.x
|View full text |Cite
|
Sign up to set email alerts
|

Age Changes in the Skeleton of the Human Lens

Abstract: The cytoskeleton of the human lens (newborn, 24 year-old and 80 year-old) was studied by morphological methods. Actin and intermediate (10 nm) filaments were identified in the epithelial cells of all the lenses. In the newborn lens intermediate filaments and chains of protein were found in cortical and nuclear fiber cells. Many intermediate filaments and protein chains in the elongated form were observed in the superficial cortical fiber cells of the 24 year-old lens. However, in the deep cortical cells the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Vimentin, as one of major cytoskeletal proteins in the lens, is expressed throughout the epithelium and elongating fiber cells of the adult mammalian lens [32,43,44]. Vimentin protein and mRNA are more abundant in the epithelium and in younger elongating fiber cells with a life-long lasting morphology [45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vimentin, as one of major cytoskeletal proteins in the lens, is expressed throughout the epithelium and elongating fiber cells of the adult mammalian lens [32,43,44]. Vimentin protein and mRNA are more abundant in the epithelium and in younger elongating fiber cells with a life-long lasting morphology [45].…”
Section: Discussionmentioning
confidence: 99%
“…Vimentin protein and mRNA are more abundant in the epithelium and in younger elongating fiber cells with a life-long lasting morphology [45]. By conventional immunocytochemical approaches, vimentin has been reported to be absent from, or at least greatly reduced in, the deeper cortical fiber cells [32,43,44]. Our current results showed that vimentin was highly expressed at both the protein and mRNA levels in the epithelium and to a lesser extent in the fiber mass of the lens, composed of the partial cortex and nucleus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In keeping with its origins from surface ectoderm, the lens placode expresses epithelial cytokeratins(Kasper and Viebahn 1992). However, after severing its connection with the ectoderm, the lens cells switch to the expression of vimentin, a well-conserved Type III IF protein common to cells of mesenchymal origin(Bradley, Ireland et al 1979; Geisler and Weber 1981; Ellis, Alousi et al 1984; Bagchi, Caporale et al 1985; Bloemendal, Willemsen et al 1985). Figures 2a–b present a localization of both vimentin protein and mRNA, highlighting its abundance in the epithelium and younger elongating fiber cells.…”
mentioning
confidence: 99%
“…By conventional immunocytochemical approaches, vimentin has been reported to be absent from, or at least greatly reduced in the deeper cortical fiber cells(Bradley, Ireland et al 1979; Ellis, Alousi et al 1984; Sandilands, Prescott et al 1995). However, any retrospective analysis of such data must bear in mind that the immunoreactivity of an antigen in the lens can be dramatically reduced in deeper cortical cells as a result of fixation approach and/or crystallin density-induced artifacts, leading to the incorrect impression that an antigen is absent or sharply reduced in deeper cells(Beebe, Vasiliev et al 2001; Yoon, Blankenship et al 2008).…”
mentioning
confidence: 99%